BARON TECHNOPARK SEBAGAI KAWASAN WISATA EDUKASI DENGAN PENDEKATAN ARSITEKTUR EKOLOGI - Maria Ulfiatun Rohmah; Musyawaroh Musyawaroh; Ummul Mustaqimah (ARSITEKTURA, 2015)
Designing of Baron Technopark based on the efforts from government Gunung Kidul in improving competitiveness for the community as well as the potential of natural resources found on Baron Beach. The purpose of this designing is to design container research and development of renewable energy and container of science and technology with effective, recreational and informative for the public like industry, researchers, educators and the general public. The main problem of this design is able to support the fulfillment of the needs of science and technology for the general public and also serves as an educational tourist attraction by paying attention to the concept of Ecological Architecture. Ecological Architecture is applied to the arrangement of buildings, building form, building color selection, materials, types of plants and utilities buildings. The result of this design from applying Ecological Architecture  is to obtain building shape based on ecological prinsiples, the material used is a material that does not have a negative impact on the environment, the choice of plants that includes four elements of Ecological Architecture (air, water, fire and earth) and the application of Ecological Architecture on water utilities, electricity and articial air. Keywords: Ecological Architecture, Baron Technopark, Renewable Energy, Educational Tourist, Gunung Kidul.